2020
DOI: 10.31703/grr.2020(v-i).06
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Leadership Style on Employees Commitment: Moderating Role of Organization Politics: A Case Study of Public Sector Universities of KPK

Abstract: The aim of this study is to investigate the relationship between employees commitment and leadership styles along with the moderating role of organizational politics in public sector universities of KPK. The researcher adopted a deductive approach with cross-sectional research design and used a quantitative methodology. Stratified random sampling has been used with an objective to ensure effective representation of the selected population. Responses from the participants were collected through a pre-structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Examples are organizational culture and employee attitudes at work, which in turn make it responsible for creating commitment among employees towards the organization. Studies have identified four of the most common leadership styles in the past that have had a strong influence on the level of commitment of employees towards their organizations, which include transformational, democratic, transactional, and autocratic leadership styles (Ali, Ali, & Sheraz, 2020).…”
Section: E) Emotional Attachmentmentioning
confidence: 99%
“…Examples are organizational culture and employee attitudes at work, which in turn make it responsible for creating commitment among employees towards the organization. Studies have identified four of the most common leadership styles in the past that have had a strong influence on the level of commitment of employees towards their organizations, which include transformational, democratic, transactional, and autocratic leadership styles (Ali, Ali, & Sheraz, 2020).…”
Section: E) Emotional Attachmentmentioning
confidence: 99%
“…The study draws impetus from extant literature (see Kumar & Krishnaraj, 2018;Yaseen et al, 2018;Abasilim et al, 2019;Ali et al, 2020;Mulugeta & Pandian, 2020) which suggests that a manager's leadership style influences employee commitment; though studies have not specifically examined the nexus of specific behaviours associated with a single leadership style and employee commitment. Interestingly, however, Oztekin et al Katsaros et al (2020) also opine that employees' commitment depends on how they view the leader and the extent to which their expectations continue to be met within the context of organisational operations.…”
Section: Introductionmentioning
confidence: 99%